2023
DOI: 10.1007/s12325-022-02414-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining Real-World Adherence to Nusinersen for the Treatment of Spinal Muscular Atrophy Using Two Large US Data Sources

Abstract: Introduction Spinal muscular atrophy (SMA) is a rare neuromuscular disease characterized by progressive muscular atrophy and weakness. Nusinersen was the first treatment approved for SMA. Per the US label, the nusinersen administration schedule consists of three loading doses at 14-day intervals, a fourth loading dose 30 days later, and maintenance doses every 4 months thereafter. Using two large US databases, we evaluated real-world adherence to nusinersen with its unique dosing schedule among ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The differences observed between nusinersen and risdiplam in adherence and persistence may also be related to different study methodologies, including how adherence and persistence were defined, datasets used, number of individuals included, and length of follow-up. As a result of the nature of the dosing administration of nusinersen, adherence can be calculated at the patient level [ 21 ], dose level [ 22 ], or both [ 20 ]. Patient-level adherence considers the adherence of each individual within the study population to estimate a population’s overall adherence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The differences observed between nusinersen and risdiplam in adherence and persistence may also be related to different study methodologies, including how adherence and persistence were defined, datasets used, number of individuals included, and length of follow-up. As a result of the nature of the dosing administration of nusinersen, adherence can be calculated at the patient level [ 21 ], dose level [ 22 ], or both [ 20 ]. Patient-level adherence considers the adherence of each individual within the study population to estimate a population’s overall adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Dose-level adherence could be highly influenced by a small number of patients contributing more doses within the analysis [ 37 ]. For example, analyses of nusinersen adherence at the dose level (e.g., Youn et al) [ 22 ] have reported higher levels of adherence to nusinersen than studies analyzing adherence at the patient level (e.g., Fox et al) [ 21 ]. Differences in adherence at the dose level (e.g., 72–76%) versus at the patient level (e.g., 27–44%) are apparent even within the same study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations